2019
DOI: 10.1108/medar-09-2018-0379
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework of tax knowledge

Abstract: Purpose This paper aims to develop a conceptual framework of tax knowledge that can be used to analyse and discuss tax knowledge as a factor influencing tax compliance. Design/methodology/approach Relevant literature was sourced using keywords pertaining to tax knowledge to identify the constructs of the framework. Thereafter, secondary interview data on small business owners’ tax challenges were thematically analysed to test the proposed framework. Findings Three elements of tax knowledge were identified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 21 publications
3
72
0
8
Order By: Relevance
“…There appears to be value in identifying the knowledge requirements of taxpayers in specific contexts or industries, as this may assist tax authorities in educating taxpayers. Bornman and Ramutumbu (2019) proposed a framework of tax knowledge that provides a structured approach for assessing tax knowledge requirements in various contexts as a factor influencing tax compliance. The framework suggests that tax knowledge is discernible in three categories: (1) general tax knowledge, (2) procedural tax knowledge and (3) legal tax knowledge.…”
Section: Tax Knowledge and Tax Compliancementioning
confidence: 99%
See 2 more Smart Citations
“…There appears to be value in identifying the knowledge requirements of taxpayers in specific contexts or industries, as this may assist tax authorities in educating taxpayers. Bornman and Ramutumbu (2019) proposed a framework of tax knowledge that provides a structured approach for assessing tax knowledge requirements in various contexts as a factor influencing tax compliance. The framework suggests that tax knowledge is discernible in three categories: (1) general tax knowledge, (2) procedural tax knowledge and (3) legal tax knowledge.…”
Section: Tax Knowledge and Tax Compliancementioning
confidence: 99%
“…The need for a conceptual framework of tax knowledge Bornman and Ramutumbu (2019) contend that there is no uniform meaning of the concept of 'tax knowledge', and there is little reference to the different elements of tax knowledge despite its importance in influencing tax compliance. Bornman and Ramutumbu (2019) examined various studies on the effect of tax knowledge on compliance, and found that authors recognise elements of tax knowledge as, for example, 'understanding laws', 'applying laws', 'reporting tax information' and 'submitting returns'. To illustrate this, findings by Palil (2010) and Saad (2014) suggest that there is a positive relationship between taxpayers' ability to understand and apply tax laws and regulations and their ability to comply.…”
Section: A Framework For Tax Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Hal itu mengharuskan pemba yar pajak untuk belajar banyak mengenai halhal yang berkaitan dengan perpajakan, tetapi tidak mudah bagi wajib pajak karena keinginan untuk belajar perpajakan sendiri harus muncul dari wajib pajak itu sendiri. Hasil penelitian di luar negeri juga tidak se jalan de ngan hasil penelitian ini, di mana penelitian dari Bornman & Ramutumbu (2019) dan Inasius (2019) yang menghasil kan data pelaku usaha kecil menengah ti dak mematuhi undangundang perpajakan. Mereka hanya memiliki pengetahuan dasar tentang pajak dan tidak memiliki pemaham an yang lebih mendalam tentang masalah perpajakan.…”
Section: Metodeunclassified
“…Besides, Eriksen and Fallan (1996) stated that knowledge influences someone's preferences and attitudes towards taxation. Previous studies (Bornman and Ramutumbu, 2019;Richardson, 2006;Chan et al 2000) reveal that the level of education and knowledge regarding tax affect positively towards taxpayer attitude and compliance level. This study argues that tax knowledge is a necessary component to led compliance.…”
Section: Introductionmentioning
confidence: 96%